Geology of the Kranzberg syncline and emplacement controls of the Usakos pegmatite field, Damara belt, Namibia - Owen, Geoffrey J. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc (Earth Sciences))--University of Stellenbosch, 2011.